Optimizing recovery strategies in elite speedskating: A comparative analysis of different modalities - Kowalski, T.; Rebis, K.; Malczewska-Lenczowska, J.; Klusiewicz, A.; Starczewski, M.; Klich, S.; Kasiak, P. (Journal of Functional Morphology and Kinesiology, 2025)
Background/Objectives: As short-track speed skaters have to race multiple races to achieve success during competition, optimizing the recovery between efforts is a noteworthy performance determinant. Therefore, we compared three different recovery modalities (active cycling recovery, pneumatic compression boots, and isocapnic breathing protocol) in the context of perceived subjective pain and recovery variables, multiple biochemical and biomechanical indices, CMJ height and power, as well as repeated efforts on the ice track. Methods: Fifteen elite short-track speed skaters (eight males and seven females; age 18.3 ± 1.0 years, height 175.6 ± 7.5 cm, weight 73.7 ± 7.7 kg, 23.8 kg/m2, VO2max 55.5 mL·kg-1·min-1: male 58 20 ± 3.6 mL·kg-1·min-1; and female 53 ± 4.5 mL·kg-1·min-1) completed the study experiment and were included in the analyses. Repeated measures ANOVA with optional post hoc Bonferroni correction was used to assess the association magnitude of changes in variables across the recovery methods. Results: All the investigated protocols were associated with significant changes in multiple recovery indices observed within all the investigated protocols (p = 0.05). However, for this sample, they resulted in analogous effects on subjective variables, hormonal response, creatine kinase, CMJ parameters, and on-ice performance (between-protocol effect: p = 0.002). Changes in creatine kinase were generally higher in males than females (p = 0.05), which might suggest that optimal recovery protocols in short-track are gender-dependent. Conclusions: Since compression and active cycling remain gold standard recovery protocols, a similar response from isocapnic breathing suggests it may be a modality particularly useful in real-world settings.